A64 TOTAL AGENESIS OF THE DORSAL PANCREAS (ADP) ASSOCIATED WITH PANCREATIC ADENOCARCINOMA: A CASE REPORT. (15th March 2019) - Evans, B; Kok, B; Wiebe, E; Mather, C; Zepeda-Gomez, S
Abstract: Background: ADP is an extremely rare congenital pancreatic anomaly and is the result of developmental failure of the dorsal pancreatic bud during embryogenesis. Partial agenesis (minor papilla, Santorini duct and body are present) is more common, total agenesis is extremely rare, with only 16 cases reported so far. In total, less than 100 cases have been reported in the literature since 1911. Aims: To describe a case of pancreatic adenocarcinoma associated with ADP. Methods: Case report. Results: A 42 year-old male patient presented with two-month weight loss and recent jaundice associated with epigastric pain. Past medical history was unremarkable. He had a 25-pack year smoking history and drank 4–5 alcoholic beverages per day. Initial workup revealed total bilirubin at 121umol/L and elevated alkaline phosphatase (952 U/L). Abdominal ultrasound showed a bulky pancreatic head and dilation of the common bile duct at 1.3cm. An abdominal CT scan showed pancreatic head enlargement and absence of the body and tail of the pancreas (small bowel-dependent sign) (Figure 1). The patient underwent an ERCP which revealed a distal common bile duct stricture with above dilation. Brushings were taken and a plastic biliary stent was placed. CA 19-9 and IgG4 levels were normal. A subsequent endoscopic ultrasound (EUS) and repeat ERCP were performed four weeks later as initial brushings showed reactive changes only. EUS guided biopsies were not feasible due to hypervascularity of the pancreatic head. During the ERCP, new biliary brushings and biopsies of the stricture were taken and a plastic stent exchange was done. The pathology results were negative again for malignancy. Hepatobiliary surgery was consulted and an MRCP was performed. This revealed absence of the main pancreatic duct. Two weeks later the patient underwent a Whipple's procedure. Intra-operatively, a firm and enlarged pancreatic head was noted as well as agenesis of the body and tail. Final pathology revealed a well-differentiated pancreatic adenocarcinoma pT2N0. Conclusions: We have described a rare case of total ADP associated with pancreatic adenocarcinoma manifested by weight loss, abdominal pain and jaundice. Sixteen cases of associated-pancreatic neoplasia have been described in ADP, this is the 10th case of pancreatic ductal adenocarcinoma. Physicians must be aware of this condition and be familiar with the previously described imaging signs associated in order to make an accurate diagnosis. Funding Agencies: None